Effect Of Predialytic and Intradialytic Oral Nutritional Supplementation On Adequacy of Hemodialysis: A Quasi-experimental Analysis - Fahad Riaz; Arshad, Abdul Rehman; Ahmed, Zubair; Iqbal, Muhammad; Saleem, Muhammad Zulqurnain; Parveen, Rabia (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare effects of predialytic and intradialytic oral nutritional supplementation on adequacy of hemodialysis. Study Design: Quasi-experimental study. Place and Duration of Study: Pak Emirates Military Hospital, Rawalpindi, Pakistan, from Jun to Aug 2023. Methodology: Patients on hemodialysis were consecutively recruited. In the first arm (two sessions), patients were given 200ml of oral NOVASOURCE® Renal two hours into dialysis sessions, whereas in the second arm (another two sessions), this was given an hour before starting the session. Serum urea levels were checked at the start and end of each dialysis session. Ultrafiltration volumes were recorded, and post-dialysis weight was noted. All patients were monitored for intradialytic hypotension. Kt/V by Daugirdas equation and urea reduction ratios were calculated. Results: Twenty patients with a median age of 57.50 years (interquartile range 35.00- 64.25 years) underwent 80 hemodialysis sessions. Mean Kt/V was 1.42± 0.38 and 1.40± 0.34 with predialytic and intradialytic nutritional supplementation (p=0.852), with targets being achieved in 27 (67.50%) and 28 (70.00%) sessions, respectively (p=0.418). Urea reduction ratios were 66.43± 16.59% and 65.82± 17.22% with predialytic and intradialytic nutritional supplementation (p=0.869), with targets being achieved in 23 (57.50%) and 26 (65.00%) sessions, respectively (p=0.973). Intradialytic hypotension was seen in 1 (0.03%) and 3 (0.08%) sessions with predialytic and intradialytic nutritional supplementation (p =0.999). Conclusion: Timing of nutritional supplementation does not affect adequacy of hemodialysis.